Kajian Potensi Wisata di Wilayah Pesisir Bulak Surabaya - Margaretha Ardhanari; Visi Saujaningati Kristyanto; Gratianus Edwi Nugrohadi (Universitas Jember, 2024)
Surabaya is a coastal city with high economic and tourism potential. Three main things that have been done by the city government (physical development, sustainable development programs, and economic strengthening) need to be noted, for example, the non-optimal management of the tourism potential of the coastal area and the imbalance between the tourist area and the surrounding fishing villages. On that basis, this research tries to answer various issues related to the optimization of tourism development in the coastal area of Bulak, Surabaya. This research is initial research that maps the various potentials (owned by the Bulak coastal area of Surabaya), which is then followed up by offering development strategies. This research used a descriptive model qualitative approach. The initial study was conducted by analyzing various planning documents, which were then followed up with field observations and interviews with key people. In the final stage, the researcher then analyzed the development strategy. The results of this study state that Bulak sub-district has nine tourism objects that have the potential to be developed in the coastal area. The proposed development strategy (based on the results of data processing) is an aggressive maintenance strategy. This is done by strengthening inward by making improvements in various fields. In addition, the development strategy also needs to be collaborative, especially with the city government, while still paying attention to various ecological issues Keywords: Tourism Potential Assessment, Aggressive Maintenance Strategy, Surabaya Coastal Area